Analisis Pengalaman Pelanggan terhadap Layanan di Bengkel Motor F21 Sinergy - Muhammad Ibni Fauzan (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze customer experience with the services provided by F21 Sinergy Motorcycle Workshop. A qualitative approach was employed, utilizing in-depth interviews and participatory observations involving 12 repeat customers who have used the workshop's services more than once. The research seeks to explore customers’ perceptions of several key service dimensions, including service quality, repair speed, the professionalism of technicians, and overall satisfaction with the repair outcomes. Findings indicate that while most customers perceive the service to be friendly and responsive, some expressed concerns regarding consistency in service speed during peak hours. The professionalism and technical competence of the mechanics were generally appreciated, particularly in terms of communication and transparency about issues and repair estimates. The study also reveals that trust and communication are critical factors that influence repeat visits and customer loyalty. Furthermore, the physical environment of the workshop, cleanliness, and waiting area comfort also contributed to the overall customer experience. These findings suggest that F21 Sinergy should maintain its strengths in interpersonal service while continuously improving operational efficiency during busy periods. This study contributes to a better understanding of how customer experience influences perceptions of service quality in the motorcycle repair industry.